PENENTUAN PENUMPULAN PISAU PADA PERMUKAAN KAYU - Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1992)
The wear of wood cutting tools. is. generally, the process which makes a usable tool unfit for continued use.  The replacement of the worn cutter by  reconditioning  or substitution of a new one represents a necessary cost which can be minimized  by controlling tool wear. Numerous  studies have been conducted through direct  observations on the cutting edge using a variety  of photographic methods. Such observations are quite complicated and can hardly be introduced to industrial practices.  This study is aimed to explore a possibility of determining  cutting  tool wear indirectly  through the work piece observation.   It is based on assumption  that knife blunting has a direct  bearing on the quality of the finished product,  i.e., changing the geometry of cutting marks on the wood surface.Boards of two wood species,  rasamala and mangium,  were seasoned to air-dry condition and planed  using new sharp knives at one feed  speed of 30 .m/min.  Observations were carried out sequentially at 5 pianing  distances, i.e., 10, 20,  40,  80 and 160 m.  Cutting marks  geometry on the wood surface  was distinguished by rubbing the surface gently with a carbon paper.  Measurements  of cutting marks and the width of cutting peak were undertaken using a digital calliper.  Results showed that values of cutting marks and width of catting peaks markedly increased with increasing planing distances.  Blunting process was significantly   affected  by wood species. Knives used for planing  rasamala boards blunied quicker than those used for  mangium.   These, to some extend, revealed  a possible use of cutting marks structure  on wood surface for  determining the wear of cutting edge.